Astin C Production by the Endophytic Fungus Cyanodermella asteris in Planktonic and Immobilized Culture Conditions. Issue 8 (5th July 2019) - Vassaux, Antoine; Tarayre, Cédric; Arguëlles‐Arias, Anthony; Compère, Philippe; Delvigne, Frank; Fickers, Patrick; Jahn, Linda; Lang, Alexander; Leclère, Valérie; Ludwig‐Müller, Jutta; Ongena, Marc; Schafhauser, Thomas; et al.
Abstract : The fungal endophyte Cyanodermella asteris ( C. asteris ) has been recently isolated from the medicinal plant Aster tataricus ( A. tataricus ). This fungus produces astin C, a cyclic pentapeptide with anticancer and anti‐inflammatory properties. The production of this secondary metabolite is compared in immobilized and planktonic conditions. For immobilized cultures, a stainless steel packing immersed in the culture broth is used as a support. In these conditions, the fungus exclusively grows on the packing, which provides a considerable advantage for astin C recovery and purification. C. asteris metabolism is different according to the culture conditions in terms of substrate consumption rate, cell growth, and astin C production. Immobilized‐cell cultures yield a 30% increase of astin C production, associated with a 39% increase in biomass. The inoculum type as spores rather than hyphae, and a pre‐inoculation washing procedure with sodium hydroxide, turns out to be beneficial both for astin C production and fungus development onto the support. Finally, the influence of culture parameters such as pH and medium composition on astin C production is evaluated. With optimized culture conditions, astin C yield is further improved reaching a five times higher final specific yield compared to the value reported with astin C extraction from A. tataricus (0.89 mg g −1 and 0.16 mg g −1 respectively). Abstract : The production of astin C, a promising anticancer and anti‐inflammatory compound initially isolated from Aster tataricus, has been recently attributed to its fungal endophyte Cyanodermella asteris . This study is the first to be dedicated to the optimization of the production of astin C by this fungus. Growing this fungus under immobilized‐cell condition increases astin C production and facilitates its purification.